LA QUÍMICA Y LA INGENIERÍA QUÍMICA EN LA LUCHA CONTRA LA CORROSIÓN DE TUBERÍAS METÁLICAS QUE CONDUCEN GAS NATURAL - Pizarro C., Raul (2005)
Chemistry and Chemical Engineering involved directly or indirectly in one of the major concerns for responsible maintenance and safety in plants extraction , transport and distribution Natural gas , which can be derived from the Natural gas leaks and / or loss of the same storage systems that contain ( tanks, piping , etc.). these leaks can cause pollution, cessation production , and a number of problems of toxicity or potential risk of fire or explosion , which cost economic rehabilitation can be very significant for the general budget operating . A serious problem represents the corrosion perforations on metal structures